Carotid Body Inflammation: Role in Hypoxia and in the Anti-inflammatory Reflex - Iturriaga, Rodrigo; Del Rio, Rodrigo; Alcayaga, Julio (My University, 2022)
Emergent evidence indicates that the carotid body (CB) chemoreceptor may sense systemic inflammatory molecules and is an afferent arm of the anti-inflammatory reflex. Moreover, a proinflammatory milieu within the CB is involved in the enhanced CB chemosensory responsiveness to oxygen following sustained and intermittent hypoxia. In this review, we focus on the physiopathological participation of CBs in inflammatory diseases, such as sepsis and intermittent hypoxia.
Keywords: carotid body; inflammation; intermittent and sustained hypoxia; obstructive sleep apnea; oxidative stress